Repeated micropulse cyclophotocoagulation in the treatment of refractory glaucoma. A clinical experience - I. E. Ioshin; A. I. Tolchinskay; I. V. Maksimov; A. V. Rakova (Российский офтальмологический журнал, 2022)
Purpose: to analyze the results of repeated micropulse transscleral cyclophotocoagulation (mTSCPC) in the treatment of refractory glaucoma (RG).Material and methods. We examined 74 patients aged 73.2 ± 6.3 years with developed (13), advanced (48) and terminal (13) stages of refractory glaucoma before and within 15 months after the first mTSCPC (SUPRA 810, Quantel Medical, France) using standard laser parameters — 100 J. According to indications, the repeated mTSCPC was performed for 17 patients. Of these, 4 patients had the second procedure three months after the first procedure, 10 patients — 6 months after it, and 3 patients, 9 months after the first procedure. The repeated mTSCPC was performed with an impact energy higher than the first one — 125 J.Results. After the first procedure, the hypotensive effect was held in 57 patients with RG (77.0 %) up to 15 months of the follow-up. The repeated mTSCPC given to 17 patients made it possible to reduce intraocular pressure (IOP) by 38.5 % for the developed RG stage, by 33.9 % for the advanced stage, and by 21.4 % at the terminal stage (p < 0.05) by 6–12 months of follow-up. The hypotensive effect was held in 13 out of 17 patients by the end of the follow-up.Сonclusion. Single and repeated mTSCPC with laser energies of 100 J and 125 J are effective and safe techniques of RH treatment. Possibly, it is worth revising the basic parameters of the mTSCPC procedure from 100 to 125 J to achieve a longer and at the same time safe hypotensive effect in patients with RG.